Indigenous Intergenerational Relational Rhythms: Sustaining Tongan Language and Culture Across Time (Tā) and Space (Vā) - Kalavite, Telesia (Art/Research International, 2024)
This article unfolds intergenerational sustainability and relational rhythms through Tongan language and culture and the interrelationships between older and younger Tongan people and between Tongans and non-Tongans in Aotearoa New Zealand (NZ). It also unpacks the interconnected ways in which Tongans as Indigenous people honour the inseparability and sensibilities of knowing–seeing–feeling–doing–being–becoming Tongan across tā–vā (time–space) in language and cultural realities, and their implications on Tongan people’s success in life. I argue that there is still space to strengthen Tongan language and culture through intergenerational relationships between Tongans in loto-Tonga, the motherland, and communities settled in tu‘a-Tonga, the diaspora such as Aotearoa NZ.